Macrofauna communities across a seascape of seagrass meadows: environmental drivers, biodiversity patterns and conservation implications - Iván F. Rodil; Andrew M. Lohrer; Karl M. Attard; Judi E. Hewitt; Simon F. Thrush; Alf Norkko (Biodiversity and Conservation, 2021)
Similar to other coastal biogenic habitats (e.g. tidal marshes, kelp forests, mangroves and coral reefs), a key function of seagrass meadows is the enhancement of biodiversity. Variability at multiple spatial scales is a driver of biodiversity, but our understanding of the response of macrofauna communities to variability of seagrass meadows is limited. We examined the macrofauna community structure (abundance and biomass) and diversity patterns (α- and β-diversity) across a seascape gradient of eleven seagrass meadows differing in the number, composition and density of plant species . The variability of the macrobenthic communities was regulated by a combination of sedimentary (mainly for the infauna) and macrophyte (mainly for the epifauna) predictors. We demonstrate that the natural occurrence of drifting algae trapped in the aboveground complexity of the meadows benefits seagrass macrofauna. Seagrass-associated macrofauna showed a clear increase in abundance and α-diversity metrics with increasing habitat complexity attributes (i.e. shoot density, plant biomass and canopy height). Furthermore, partitioning of β-diversity (i.e. the variation of species composition between sites) implied the replacement of some species by others between sites (i.e. spatial turnover) instead of a process of species loss (or gain) from site to site (i.e. nestedness). Therefore, the enhancement of macrofauna diversity across an increasing gradient of seagrass complexity, and the dominance of the turnover component suggest that devoting conservation efforts on many different types of meadows, including the less diverse, should be a priority for coastal habitat-management.